IMPLEMENTASI E- SAMSAT UNTUK MEMBANGUN KEPERCAYAAN DAN KEPATUHAN PAJAK KENDARAAN BERMOTOR - Sri Rahayu; Barkah Rosadi; Muhammad Yusuf Alhadihaq (Journal Publicuho, 2023)
The research objective is to evaluate the implementation of E-Samsat as a tool to build trust and increase taxpayer compliance in paying motor vehicle taxes. The research method is a causal study with a questionnaire as a data collection tool. The affordable sample in this study is motor vehicle taxpayers who use E-Samsat in Bandung Regency, as many as 227. Inferential analysis to test the relationship of variables using covariant SEM with SPSS tools 25 The results show that using E-Samsat positively relates to trust and compliance taxpayers in paying motor vehicle tax. E-Samsat can increase the trust and compliance of taxpayers in paying motor vehicle taxes. E-Samsat can be an effective solution to increase taxpayer trust and compliance in paying motor vehicle taxes. The practical implication of this research is that the government and tax agencies can increase the use of E-Samsat to build trust and increase taxpayer compliance in paying motor vehicle taxes. This research can also be the basis for further research on the use of technology in improving tax compliance and public financial management.